CBCT study on the safe location of palatal microscrew implant anchorage nail between maxillary first and second molars - LI Xinghan (Editorial Department of Journal of Prevention and Treatment for Stomatological Diseases, 2022)
Objective Conebeam CT (CBCT) was used to measure the palatine between the maxillary first and second molars. The proximal and distal palatal widths of the maxillary first and second molar and the palatal mucosal thickness and bone tissue thickness when microscrew implant anchorage nail were implanted at different angles provided a reference for the clinical selection of microscrew implant placement. Methods The image data of 90 adult patients were selected as the research object, and the jaw bone was reconstructed by scanning. In maxillary palatine, selection of distances at 12 mm, 14 mm, 16 mm, and 18 mm from the palatal apex of maxillary first molar between the maxillary first and second molar were used as measurement, measured the proximal and distal palatal widths of maxillary first and second molar and the palatal mucosal thickness and bone tissue thickness when microscrew implant anchorage nails were implanted at 30 °, 45 °, 60 °, and 90 °. SPSS 26.0 software was used for one-way ANOVA and LSD pair comparison. Results The larger the angle of the microscrew implant anchorage nail was, the smaller the proximal and distal medial widths between the maxillary first and second molar, and the difference was statistically significant (P < 0.05). Compared with the 90° direction, the proximal and distal medial widths of the microscrew implant anchorage nail were larger in the 60° direction. The greater the angle of implantation, the smaller the mucosal thickness and the greater the bone tissue thickness, and the results showed a significant difference (P < 0.001). Compared with the direction of 30° and 45°, the mucosal thickness at the direction of 60° was smaller, and the bone tissue thickness was larger. The higher the position of the microscrew implant anchorage nail, the greater the width of the proximal and distal medial, and the difference was statistically significant (P < 0.05). Compared with the positions 12 and 14 mm from the palatal tip, the proximal and distal medial widths of the microscrew implant anchorage nail were larger. The higher the implant position was, the greater the mucosal thickness and the smaller the bone tissue thickness. The results showed a significant difference (P < 0.001). Compared with the position of 18 mm from the palatal tip of the maxillary first molar, the mucosal thickness was smaller and the bone tissue thickness was larger. Conclusion It is most appropriate to implant microscrew implant anchorage nail at least 10 mm in length in the direction of 60° at the palatal apex 16 mm from the maxillary first molar in palatine between the first and second molar.